93 Effects of a Functional Oils Blend on Intestinal Health and Growth Performance of Nursery Pigs - Moita, Vitor Hugo C (J Anim Sci, 2021)
This study was to investigate the role of castor oil and cashew nutshell liquid (functional oil blend, FOB) on intestinal health and growth performance of nursery pigs and to determine an optimal supplemental level. Newly weaned pigs (20 barrows and 20 gilts at 25 d of age, 7.02 ± 0.58 kg BW) were randomly allotted to 5 treatments in a RCBD and fed in 2 phases (13 and 21 d respectively) with increasing levels (0, 0.050, 0.075, 0.100, and 0.150%) of FOB. Growth performance was measured by each phase. Titanium dioxide (0.4%) was added to phase 2 diets as an indigestible marker to measure AID. On d 34, all pigs were euthanized to collect jejunum to measure immune status, oxidative stress status, microbiota, morphology, and crypt cell proliferation. Data were analyzed using Proc Mixed of SAS. Supplementation of FOB did not affect the overall growth performance. Supplementation of FOB tended to decrease (P = 0.064) the concentration of jejunal protein carbonyl (3.11 to 2.45 nmol/protein) and tended to increase villus height (P = 0.098, 401 to 453 μm) and crypt depth (P = 0.070, 86 to 99 μm). Increasing FOB reduced (P < 0.05) relative abundance of Helicobacteraceae (46.8 to 21.0%) and increased (P < 0.05) relative abundance of Prevotellaceae (7.9 to 13.1%), Burkholderiaceae (6.3 to 10.8%) and Pseudomonadaceae (0.1 to 1.0%), and increased (P < 0.05) alpha diversity of the jejunal mucosa-associated microbiota at the family level (Chao1 index 42.8 to 56.8%). In conclusion, FOB showed potential benefits on intestinal health of nursery pigs by increasing beneficial and reducing harmful bacteria reducing oxidative damages in the jejunal mucosa, and by enhancing villus structure, whereas without affecting the growth performance. The FOB at a range of 0.050% to 0.150% provided the most benefit for nursery pigs.